Moral Philosophy in Ibn Miskawaih's Thought and Its Relevance to the Digital Moral Crisis - Siregar, Hamdan (Indonesian Journal of Islamic History and Culture, 2026)
The rapid advancement of Society 5.0 has created a digital paradox: technological connectivity has increased, yet moral degradation manifested in cyberbullying, hoaxes, and digital hedonism (flexing) has escalated. Existing legal regulations are often insufficient to address the root causes of these behaviors, which lie in the spiritual and psychological realms. This study aims to explore the relevance of Ibnu Miskawaih's moral philosophy as a fundamental solution to the modern digital moral crisis. This research employs a qualitative method with a library research design, utilizing a hermeneutic approach adapted from the "Research Onion" framework. The primary data source is the book Tahdhib al-Akhlaq wa Tathir al-A'raq. The findings reveal that Miskawaih’s concept of Al-Wasath (The Golden Mean) serves as a relevant "soul therapy" (Tibb al-Nufus) for digital users. Specifically, the harmonization of the soul's faculties offers ethical solutions: Al-Hikmah (Wisdom) to counter disinformation, Al-'Iffah (Temperance) to restrain digital consumerism, and Al-Syaja'ah (Courage) to manage anger in online interactions. The study concludes that integrating Miskawaih’s philosophy into digital literacy is essential for building internal self-defense mechanisms against moral decadence in the cyber world.